2005
DOI: 10.1091/mbc.e04-10-0938
|View full text |Cite
|
Sign up to set email alerts
|

dGRASP Localization and Function in the Early Exocytic Pathway inDrosophilaS2 Cells

Abstract: The de novo model for Golgi stack biogenesis predicts that membrane exiting the ER at transitional ER (tER) sites contains and recruits all the necessary molecules to form a Golgi stack, including the Golgi matrix proteins, p115, GM130, and GRASP65/55. These proteins leave the tER sites faster than Golgi transmembrane resident enzymes, suggesting that they act as a template nucleating the formation of the Golgi apparatus. However, the localization of the Golgi matrix proteins at tER sites is only shown under c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
121
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(127 citation statements)
references
References 61 publications
6
121
0
Order By: Relevance
“…It is interesting to notice that, for few of them, the N-terminal MYR alone without any evident second signal has been shown to target these proteins to intracellular membrane compartments with the ER/Golgi complex being the most frequent localization observed (Resh, 2006). For instance, this is the case for proteins such as eNos (Liu et al, 1997), GRASP (Kondylis et al, 2005), and the Arl family (Price et al, 2005;Sahin et al, 2008). Relocalization at the ER/Golgi compartment from the PM was also observed when the second signal of several known MYRed proteins was abolished, as in the Fyn and Yes protein kinases, in which the Cys residues necessary for the PAL were substituted by a Ser or the polybasic domain of Src protein kinase was made shorter (McCabe and Berthiaume, 1999).…”
Section: Proteins Displaying Only An N-terminal Myred Site: the Plantmentioning
confidence: 99%
“…It is interesting to notice that, for few of them, the N-terminal MYR alone without any evident second signal has been shown to target these proteins to intracellular membrane compartments with the ER/Golgi complex being the most frequent localization observed (Resh, 2006). For instance, this is the case for proteins such as eNos (Liu et al, 1997), GRASP (Kondylis et al, 2005), and the Arl family (Price et al, 2005;Sahin et al, 2008). Relocalization at the ER/Golgi compartment from the PM was also observed when the second signal of several known MYRed proteins was abolished, as in the Fyn and Yes protein kinases, in which the Cys residues necessary for the PAL were substituted by a Ser or the polybasic domain of Src protein kinase was made shorter (McCabe and Berthiaume, 1999).…”
Section: Proteins Displaying Only An N-terminal Myred Site: the Plantmentioning
confidence: 99%
“…GRASP65 was first described by Barr, Warren and colleagues as a Golgi cisternal stacking factor using an in vitro Golgi reassembly assay. 49 However, RNAi studies have later shown that its main function may not be in cisternal stacking, [50][51][52] but in the formation and/or maintenance of the tubules connecting the stacks within the Golgi ribbon. 52 GRASP65 is a major mitotically-phosphorylated Golgi protein.…”
Section: The Golgi Mitotic Checkpoint Is Regulated By the Golgi Ribbomentioning
confidence: 99%
“…Previous work has shown that RNAi depletion of the single Drosophila GRASP homologue (dGRASP) or its partner dGM130 does not lead to an apparent separation of the paired Golgi stacks. 12,51 Furthermore, the single CtBP/BARS homologue that exists in Drosophila (dCtPB) has been shown to mediate transcription repression regulating embryonic development, [67][68] but thus far, no link to the Golgi organization has been reported.…”
Section: The Golgi Ribbon Unlinking G 2 /M Checkpoint Is Conserved Inmentioning
confidence: 99%
“…In recent years, with the advent of RNAi-based technologies, knock-down studies have broadly confirmed a role for GRASP proteins and Golgins in controlling Golgi morphology but have not agreed with each other on many notable details, leaving the field in a somewhat confused and conflictory state (10,(15)(16)(17)(18)(19)(20). In the simpler case of Drosophila, dsRNA-mediated depletion of dGRASP results in ∼30% loss of Golgi stacks, whereas double depletion of dGRASP and dGM130 was shown to unstack the Golgi, as examined by EM (21). In Schizosaccharomyces pombe, depletion of yeast GRASP homolog Grh1 has no effect on Golgi stacking (22).…”
mentioning
confidence: 99%